2019
DOI: 10.1080/17461391.2019.1689300
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions to prevent hamstring injuries in athletes: A systematic review and meta‐analysis

Abstract: The aim of this meta-analysis was to assess the effectiveness of exercise-based interventions for prevention of hamstring injuries in sport. PubMed, Cochrane Central Register of Controlled Trials, Web of Science, ResearchGate, CINAHL, PEDro, ScienceDirect and Google Scholar databases were searched for randomized controlled trials and prospective cohort studies exploring the effects of exercise interventions on hamstring injury incidence. Subgroup analyses were performed to determine effects of several independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 66 publications
1
22
0
1
Order By: Relevance
“…Two overlapping systematic reviews 80 , 203 published in 2015 and 2017, respectively, found that using a YoYo flywheel ergometer for eccentric hamstring strengthening was effective at reducing hamstring injuries in soccer players. In 2019, Vatovec et al 247 conducted a meta-analysis of 17 studies and found that hamstring injuries were reduced by 51% after exercise interventions and by 50% after neuromuscular interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two overlapping systematic reviews 80 , 203 published in 2015 and 2017, respectively, found that using a YoYo flywheel ergometer for eccentric hamstring strengthening was effective at reducing hamstring injuries in soccer players. In 2019, Vatovec et al 247 conducted a meta-analysis of 17 studies and found that hamstring injuries were reduced by 51% after exercise interventions and by 50% after neuromuscular interventions.…”
Section: Resultsmentioning
confidence: 99%
“…‡‡ Neuromuscular, 34 , 35 , 250 balance, 25 , 34 , 48 , 143 , 197 and exercise training 50 , 83 have also been shown to be effective for reducing ankle injuries. Exercise and neuromuscular training have been demonstrated to be effective at reducing hamstring injuries by 50% 247 ; however, the effectiveness of strengthening remains uncertain, 78 , 80 , 101 , 203 and there is no evidence to support stretching 145 , 186 for hamstring injury prevention. Lower extremity injuries can be reduced by exercise 33 , 261 and neuromuscular training 58 , 95 , 221 , 231 programs, and the risk for stress fractures may be reduced by foot orthoses.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of athletes' background and competition levels, hamstring exercises could reduce hamstring strains by 50% on average. [37][38][39] Sports medicine specialists and coaches should incorporate hamstring exercises gradually for high school basketball athletes for their athletic performance development as well as hamstring strain injury prevention purposes with proper progressions. 40 Eccentric exercises have been commonly used during rehabilitation of tendinopathies, muscle strains, and anterior cruciate ligament post-operation.…”
Section: Discussionmentioning
confidence: 99%
“…The focus has relied on injury prevention, although we prefer terms such as “risk mitigation,” since there is always an inherent injury risk. A systematic review with meta-analysis (SRMA) including 17 studies showed that exercise-based interventions reduced hamstrings injury risk in ∼50% ( Vatovec et al, 2020 ). However, the quality of assessment through the PEDro (Physiotherapy Evidence Database) scale showed major problems in many studies, with nine having a classification ≤4 (i.e., low methodological quality), and none presenting a classification above six points in the PEDro scale (i.e., no study with high quality).…”
Section: Part 1: An Overview Of Hamstrings Injuriesmentioning
confidence: 99%
“…Weekly frequency of exercise-based programs to mitigate injury risk is an important parameter: interventions performed ≥2 times per week were more effective in reducing hamstrings injury risk than interventions performed <2 times per week, even though the differences were not large ( Vatovec et al, 2020 ). Previous research suggested that the compliance to the program (i.e., adhering to and performing the sessions) is an important prognostic factor regarding injury risk ( Goode et al, 2015 ; Chebbi et al, 2020 ).…”
Section: Part 1: An Overview Of Hamstrings Injuriesmentioning
confidence: 99%